Genetic structure in the seabuckthorn carpenter moth (Holcocerus hippophaecolus) in China: the role of outbreak events, geographical and host factors. - Jing Tao; Min Chen; Shi-Xiang Zong; You-Qing Luo (PLoS ONE, 2012)
Understanding factors responsible for structuring genetic diversity is of fundamental importance in evolutionary biology. The seabuckthorn carpenter moth (Holcocerus hippophaecolus Hua) is a native species throughout the north of China and is considered the main threat to seabuckthorn, Hippophae rhamnoides L. We assessed the influence of outbreaks, environmental factors and host species in shaping the genetic variation and structure of H. hippophaecolus by using Amplified Fragment Length Polymorphism (AFLP) markers. We rejected the hypothesis that outbreak-associated genetic divergence exist, as evidenced by genetic clusters containing a combination of populations from historical outbreak areas, as well as non-outbreak areas. Although a small number of markers (4 of 933 loci) were identified as candidates under selection in response to population densities. H. hippophaecolus also did not follow an isolation-by-distance pattern. We rejected the hypothesis that outbreak and drought events were driving the genetic structure of H. hippophaecolus. Rather, the genetic structure appears to be influenced by various confounding bio-geographical factors. There were detectable genetic differences between H. hippophaecolus occupying different host trees from within the same geographic location. Host-associated genetic divergence should be confirmed by further investigation.